1-Methylcyclopropene treatment followed with ethylene treatment alleviates postharvest chilling injury of 'Xuxiang' kiwifruit during low-temperature storage. (December 2021) - Liu, Hui; Pei, Huahua; Jiao, Jianqing; Jin, Mijing; Li, Huan; Zhu, Qinggang; Ma, Yanping; Rao, Jingping
Abstract: Kiwifruit, a cold-sensitive fruit, often suffers chilling injury (CI) during low-temperature storage. Ethylene plays an important role in regulating cold tolerance in many types of fruit postharvest. However, the effect of ethylene treatment alone or 1-methylcyclopropene (1-MCP) combined with ethylene treatment on CI in harvested kiwifruit under low temperatures remains unclear. In this study, four treatments (air; 1 μL L −1 ethylene; 0.25 μL L −1 1-MCP; and 0.25 μL L −1 1-MCP combined with 1 μL L −1 ethylene) were applied to 'Xuxiang' kiwifruit at 20 °C, which were then stored at 0 °C for up to 100 d. Indicators related to the CI of kiwifruit were then evaluated. The results showed that 1 μL L −1 ethylene treatment accelerated the development of CI, with this treatment resulting in the most serious water-soaked appearance and the highest lignin content in pulp tissue among the four treatments and increasing the endogenous production of ethylene, the relative leakage of electrolytes and malondialdehyde (MDA) content. The combination treatment (0.25 μL L −1 1-MCP + 1 μL L −1 ethylene) alleviated CI of 'Xuxiang' kiwifruit during low-temperature storage, enhanced the chilling tolerance of kiwifruit by decreasing electrolyte leakage and MDA content to maintain membrane integrity and increased the activities of catalase (CAT) and ascorbate peroxidase (APX). The results of this study reveal a possible superior storage method for 'Xuxiang' kiwifruit that allows longer storage than existing methods while maintaining fruit quality: 0.25 μL L −1 1-MCP treatment followed with 1 μL L −1 ethylene treatment and storage at a low temperature. Highlights: The 1 μL L −1 ethylene treatment accelerated the CI in 'Xuxiang' kiwifruit. The combined treatment of 0.25 μL L −1 1-MCP and 1 μL L −1 ethylene alleviated CI. Combined treatment alleviated CI by holding membrane integrity & antioxidant activity.